Immunogold electron microscopy and confocal analyses reveal distinctive patterns of histone H3 phosphorylation during mitosis in MCF‐7 cells. Issue 4 (22nd January 2016) - Yan, Yitang; Cummings, Connie A.; Sutton, Deloris; Yu, Linda; Castro, Lysandra; Moore, Alicia B.; Gao, Xiaohua; Dixon, Darlene
Abstract : Histone phosphorylation has a profound impact on epigenetic regulation of gene expression, chromosome condensation and segregation, and maintenance of genome integrity. Histone H3 Serine 10 is evolutionally conserved and heavily phosphorylated during mitosis. To examine Histone H3 Serine 10 phosphorylation (H3S10ph) dynamics in mitosis, we applied immunogold labeling and confocal microscopy to visualize H3S10ph expression in MCF‐7 cells. Confocal observations showed that MCF‐7 cells had abundant H3S10ph expression in prophase and metaphase. In anaphase, the H3S10ph expression was significantly decreased and displayed only sparsely localized staining that mainly associated with the chromatid tips. We showed that immunogold bead density distribution followed the H3S10ph expression patterns observed in confocal analysis. At a higher magnification in metaphase, the immunogold beads were readily visible and the bead distribution along the condensed chromosomes was distinctive, indicating the specificity and reliability of the immunogold staining procedure. In anaphase, the beads were found to distribute focally in specific regions of chromatids, reinforcing the confocal observations of differential H3 phosphorylation. To our knowledge, this is the first report to show the specific H3S10ph expression with an immunogold technique and transmission electron microscopy. Additionally, with confocal microscopy, we analyzed H3S10ph expression in an immortalized cell line derived from benign uterine smooth muscle tumor cells. H3S10ph epitope was expressed more abundantly during anaphase in the benign tumor cells, and there was no dramatic differential expression within the condensed chromatid clusters as observed in MCF‐7 cells. The differences in H3S10ph expression pattern and dynamics may contribute to the differential proliferative potential between benign tumor cells and MCF‐7 cells. Published 2016. This article is a U.S. Government work and is in the public domain in the USA